ОПТИМИЗАЦИЯ ЭНЕРГОСИСТЕМ С ИСПОЛЬЗОВАНИЕМ ГЕНЕТИЧЕСКОГО АЛГОРИТМА: ЭФФЕКТИВНОСТЬ, УСТОЙЧИВОСТЬ И УПРАВЛЕНИЕ В ДИНАМИЧНОЙ СРЕДЕ - Сафарова, Л.У. (SCIENCE and SOCIETY, 2024)
The research in this paper presents a method for optimizing power systems using a genetic algorithm that takes into account the complex relationships in the power infrastructure. The genetic algorithm provides flexibility and versatility for global optimization, adapting to system dynamics and being robust to local minima. The method is used to optimize the energy balance, minimize costs and take into account the nonlinear characteristics of the power system. The experimental results confirmed the effectiveness of the method, demonstrating high accuracy and the ability to balance energy resources while taking into account complex conditions. However, further improvement requires a more in-depth analysis of the influence of the algorithm parameters and taking into account additional uncertainty factors. This research provides significant insights into the field of power system optimization and serves as a basis for developing more effective control methods in dynamic energy environments.